Negative Affect Instability Among Individuals With Comorbid Borderline Personality Disorder and Posttraumatic Stress Disorder. (January 2016) - Scheiderer, Emily M.; Wang, Ting; Tomko, Rachel L.; Wood, Phillip K.; Trull, Timothy J.
Ecological momentary assessment was utilized to examine affective instability (AI) in the daily lives of outpatients with borderline personality disorder (BPD; N = 78), with and without posttraumatic stress disorder (PTSD). A psychiatric control group ( n = 50) composed of outpatients with major depressive disorder/dysthymia (MDD/DYS) was employed to compare across subgroups: BPD-only, BPD+PTSD, MDD/DYS-only, and MDD/DYS+PTSD. Compared with the BPD-only group, the BPD+PTSD group had significantly greater instability of fear and sadness, but did not significantly differ in instability of hostility or aggregate negative affect. This pattern of elevated instability of fear and sadness was not present—and, in fact, was reversed—in the MDD/DYS group. Results emphasize the importance of examining AI within the context of specific comorbidities and affect types. Treatment and research addressing AI in the context of BPD-PTSD comorbidity may benefit from a focus on fear and sadness as separate from hostility or general negative affect.